Peran Media Sosial Sebagai Promosi Pemanfaatan Jasa Informasi di Perpustakaan Universitas Islam Negeri Imam Bonjol Padang - Shinta Nofita Sari; Nurul Salma (Universitas Sebelas Maret Library, 2024)
Leaders are responsible for the organization's progress based on the vision, mission, and goals of the organization they lead. This paper analyzes the leadership style of female library heads using the theory of Behavioral Mahakumaran. A leader will be a role model or example for librarians under him. The leadership style also determines the direction of the library's goals. The purpose of this study is to describe the leadership style of female head librarians at the Bali International Polytechnic Library. This type of research is field research. The data collection techniques used are observation, documentation, and interviews. The data obtained in the study were analyzed using the theory of behavioral Mahakumaran. The results of this study show that the Head of the Bali International Polytechnic Library has a leadership style that combines authoritative, affiliative, democratic, and coaching.